2008
DOI: 10.1111/j.1532-5415.2008.02040.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Educational Level on Polypharmacy and Inappropriate Drug Use: A Register‐Based Study of More Than 600,000 Older People

Abstract: Low educational attainment was associated with a greater likelihood of poypharmacy, excessive polypharmacy, and potential IDU in elderly Swedish persons, even after controlling for age, sex, place of residence, and comorbidity. Women with low education had slightly higher likelihood of receiving polypharmacy and potential IDU than men with low education. The recently established SPDR may be useful for continuous monitoring and for designing interventions to improve drug quality in low-educated elderly people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
183
4
11

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(220 citation statements)
references
References 38 publications
22
183
4
11
Order By: Relevance
“…Concerns about polypharmacy include increased ADRs, drug interactions, prescribing cascade and higher costs [23]. Polypharmacy is often associated with a decreased quality of life, decreased mobility and cognition [24].…”
Section: Discussionmentioning
confidence: 99%
“…Concerns about polypharmacy include increased ADRs, drug interactions, prescribing cascade and higher costs [23]. Polypharmacy is often associated with a decreased quality of life, decreased mobility and cognition [24].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we were not able to include variables that are not routinely captured in the claims database, such as tobacco or alcohol consumption. Finally, because the NHIRD only recorded up to 5 diagnoses per patient visit, 18 we may have underestimated the prevalence of comorbidities in our cohort.…”
Section: Limitationsmentioning
confidence: 99%
“…17 We defined polypharmacy and excessive poly pharmacy as the concomitant use of 5 or more and 10 or more drugs, respectively, based on previous studies. 7,18 We defined potentially inappropriate medications using the 2012 update to the Ameri can Geriatrics Society's Beers Criteria.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Age is the strongest predictor for using several drugs and polypharmacy (defined as a daily intake of five or more specific drugs) is common among older people. Haider et al [2] investigated the drug use of 626 258 people in Sweden aged 75 -89 and found that polypharmacy occurred in 57% of the sample and that 18% had a daily intake of ten or more specific drugs. Polypharmacy was also more common among those of low socioeconomic status indicating that patient education F o r P e e r R e v i e w 4 interventions targeting this group could be important.…”
Section: Introductionmentioning
confidence: 99%
“…polypharmacy [2], medication errors [3], inappropriate drug use (i.e prescription of drugs that might be especially harmful to older people) [4] and adherence [5]. Age is the strongest predictor for using several drugs and polypharmacy (defined as a daily intake of five or more specific drugs) is common among older people.…”
Section: Introductionmentioning
confidence: 99%